TOWARDS SUSTAINABLE PRACTICES: A COMPARATIVE STUDY OF JAPANESE, ITALIAN, AND ALGERIAN HOUSEHOLD WASTE MANAGEMENT MODELS - Menadi Nerdjes; Alkama Djamel; Bouadam Roukia (International Journal of Innovative Technologies in Social Science, 2024)
Household waste management varies significantly across countries, as illustrated by the examples of Kamikatsu in Japan, Capannori in Italy, and Algeria. Kamikatsu has implemented a highly detailed waste sorting system that actively involves the local community, significantly reducing the amount of waste sent to landfills. In Italy, Capannori has adopted a zerowaste approach through policies such as door-to-door collection and reuse centers, achieving a high recycling rate. These initiatives highlight the importance of decentralization and citizen participation for effective waste management. In Algeria, however, waste management remains largely standardized, hindering the development of effective local solutions. Compared to the Japanese and Italian models, it appears that greater citizen involvement and more autonomous local governance could serve as key levers to improve waste management in Algeria. These examples underline the need for enhanced citizen engagement.